Beispiel Nr: 13
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1\frac{1}{2} x -2 y =9\\ \frac{2}{5} x +\frac{1}{3} y = 5 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1\frac{1}{2} x -2 y =9\\ II \qquad \frac{2}{5} x +\frac{1}{3} y = 5 \\ \text{I nach y auflösen}\\ 1\frac{1}{2} x -2 y =9 \\ 1\frac{1}{2} x -2 y =9 \qquad /-1\frac{1}{2} x\\ -2 y =9 -1\frac{1}{2} x \qquad /:\left(-2\right) \\ y =-4\frac{1}{2} +\frac{3}{4} x \\ \text{II nach y auflösen}\\ \frac{2}{5} x +\frac{1}{3} y =5 \\ \frac{2}{5} x +\frac{1}{3} y =5 \qquad /-\frac{2}{5} x\\ \frac{1}{3} y =5 -\frac{2}{5} x \qquad /:\frac{1}{3} \\ y =15 -1\frac{1}{5} x \\ \text{I = II}\\ -4\frac{1}{2} +\frac{3}{4} x =15 -1\frac{1}{5} x \qquad /-\frac{3}{4} x /-15 \\ -4\frac{1}{2}-15 =-1\frac{1}{5} x -\frac{3}{4} x \\ -19\frac{1}{2} =-1\frac{19}{20} x \qquad /:\left(-1\frac{19}{20}\right) \\ x=10 \\ \text{x in I}\\ y =-4\frac{1}{2} +\frac{3}{4} \cdot 10 \\ y=3 \\ L=\{10/3\} \end{array} & \begin{array}{l} I \qquad 1\frac{1}{2} x -2 y =9\\ II \qquad \frac{2}{5} x +\frac{1}{3} y = 5 \\ \text{I nach x auflösen}\\ 1\frac{1}{2} x -2 y =9 \\ 1\frac{1}{2} x -2 y =9 \qquad /+2 y\\ 1\frac{1}{2} x =9 +2 y \qquad /:1\frac{1}{2} \\ x =6 +1\frac{1}{3} y \\ \text{II nach x auflösen}\\ \frac{2}{5} x +\frac{1}{3} y =5 \\ \frac{2}{5} x +\frac{1}{3} y =5 \qquad /-\frac{1}{3} y\\ \frac{2}{5} x =5 -\frac{1}{3} y \qquad /:\frac{2}{5} \\ x =12\frac{1}{2} -\frac{5}{6} y \\ \text{I = II}\\ 6 +1\frac{1}{3} y =12\frac{1}{2} -\frac{5}{6} y \qquad /-1\frac{1}{3} y /-12\frac{1}{2} \\ 6-12\frac{1}{2} =-\frac{5}{6} y -1\frac{1}{3} y \\ -6\frac{1}{2} =-2\frac{1}{6} y \qquad /:\left(-2\frac{1}{6}\right) \\ y=3 \\ \text{y in I}\\ x =6 +1\frac{1}{3} \cdot 3 \\ x=10 \\ L=\{10/3\} \end{array} \end{array} $